PENGARUH MOTIVASI, DISIPLIN DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR TENAGA OUTSOURCING DI DINAS PENDAPATAN DAN PENGELOLAAN KEUANGAN KOTA SURABAYA - Farahiyah Eki Riantini; Sandra Iriawan (UNEJ e-Proceeding)
This study aimed to detect the effect of the extent of motivation, discipline and job satisfaction of the current can improve the behavior of organizational citizenship behavior (OCB) outsourced personnel in the Department of Revenue and Financial Management (DRFM) Surabaya. In this study a model of analysis was Multiple Linear Regression Analysis. The population was outsourced staff of DRFM Surabaya, which amounted to 300 people. The determination of the sample was using the method Slovin, i.e. 75 outsourced staffs. Data collection techniques used was observation, interview and spreading questionnaires. The analysis showed variable work motivation, Work Discipline and job satisfaction, simultaneously significant effect on OCB. The results of the analysis which found a significant and positive influence motivation, discipline and job satisfaction partially on OCB outsourced personnel, proves that behavior improvement OCB outsourced personnel may be shaped by their motivation, discipline and job satisfaction. Variable Work Discipline provides the most dominant influence on OCB.